2017
DOI: 10.3389/fpsyg.2017.00523
|View full text |Cite
|
Sign up to set email alerts
|

Are Psychology Journals Anti-replication? A Snapshot of Editorial Practices

Abstract: Recent research in psychology has highlighted a number of replication problems in the discipline, with publication bias – the preference for publishing original and positive results, and a resistance to publishing negative results and replications- identified as one reason for replication failure. However, little empirical research exists to demonstrate that journals explicitly refuse to publish replications. We reviewed the instructions to authors and the published aims of 1151 psychology journals and examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
82
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(87 citation statements)
references
References 34 publications
1
82
0
4
Order By: Relevance
“…In the current study, a battery of binarized matrices rather than weighted networks was produced for graph-theoretical analysis, providing the fairly realistic arithmetical operator to brain connectomes (Rubinov et al, 2009). Aside from this, the pre-registration for the methodological designs (e.g., statistical model) of the research is increasingly prevalent in the both psychological and brain science to address the potential reproducibility crisis stemming from the multiple comparisons (Lindsay, 2015;Martin & Clarke, 2017). As a result, it is still valuable to further explore this issue in the context of weighted networks.…”
Section: Methodological Concernsmentioning
confidence: 99%
“…In the current study, a battery of binarized matrices rather than weighted networks was produced for graph-theoretical analysis, providing the fairly realistic arithmetical operator to brain connectomes (Rubinov et al, 2009). Aside from this, the pre-registration for the methodological designs (e.g., statistical model) of the research is increasingly prevalent in the both psychological and brain science to address the potential reproducibility crisis stemming from the multiple comparisons (Lindsay, 2015;Martin & Clarke, 2017). As a result, it is still valuable to further explore this issue in the context of weighted networks.…”
Section: Methodological Concernsmentioning
confidence: 99%
“…The quantity of replication is, perhaps, influenced by the extent to which journals encourage or discourage replication. To investigate how psychology journals approach this issue, Martin and Clarke (2017) reviewed the scope sections of author guidelines of 1,151 journals and found that 63% did not state that they accepted replications, but neither did they discourage them; 33% implicitly discouraged them by emphasizing originality, novelty, or innovation of submissions; 3% of journals stated that they accepted them; and 1% actively discouraged replications by stating that they did not publish them. The fact that only 3% of journals stated that they accepted replications may partly be due to the perceived impact, and hence prestige, of replication.…”
Section: The Quantity Of Replication Researchmentioning
confidence: 99%
“…Beyond these calls, efforts to actively promote and facilitate replication studies have also emerged. For example, the Instruments for Research into Second Languages (IRIS) repository (http://www.iris-database.org) was established in 2011 and holds, at the time of writing, over 3,800 materials that can be used for replication, among other purposes, in L2 research (Marsden & Mackey, 2014;Marsden, Mackey, & Plonsky, 2016 infrastructure to facilitate collaboration and has been used for large replication efforts in psychology (e.g., Open Science Collaboration, 2015), which continue to make waves in academia (Laws, 2016;Lindsay, 2015;Martin & Clarke, 2017) and the general media (Baker, 2015;Devlin, 2016). In some fields, a flourishing metascience, that is, the scientific study of science (see Munafò et al, 2017), has included syntheses assessing the quantity and nature of replication efforts, for example, in education (Makel & Plucker, 2014) and in psychology (Makel et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…But there is still a lot of room for improvement. In a recent review of 1151 journals, researchers found that only 3% explicitly stated that they accepted replications; 63% did not state as much but also did not discourage them; 33% discouraged them implicitly by stressing novelty in solicited submissions; and 1% actively frowned on replications by stating that they did not publish them [43]. Against this backdrop, where does the Journal of Clinical and Translational Research (JCTR) stand?…”
mentioning
confidence: 99%